2010
DOI: 10.1139/w10-061
|View full text |Cite
|
Sign up to set email alerts
|

Development and pilot evaluation of a novel probiotic mixture for the management of seasonal allergic rhinitis

Abstract: Microbial exposure may direct the immune system away from allergic-type responses, but until now probiotic interventions have had limited success in the prevention and treatment of allergic diseases. In this study, a novel probiotic mixture was specifically created based on preliminary in vitro investigations on pollen-induced immune responses. A mixture with Lactobacillus rhamnosus GR-1 and a novel fecal Bifidobacterium adolescentis isolate was formulated into a yogurt and tested for its effects in 36 subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…A fourth study, testing an ad hoc mixture of L. rhamnosus GR-1 and Bifidobacterium adolescentis supplied in a yogurt, found no clinical effect in a group of adult patients with ragweed-induced allergic rhinitis. However, potential desirable effects were found in the cytokine profiles of these patients, albeit without a clinical symptom tie-in [105]. …”
Section: Probiotics and Respiratory Allergymentioning
confidence: 99%
“…A fourth study, testing an ad hoc mixture of L. rhamnosus GR-1 and Bifidobacterium adolescentis supplied in a yogurt, found no clinical effect in a group of adult patients with ragweed-induced allergic rhinitis. However, potential desirable effects were found in the cytokine profiles of these patients, albeit without a clinical symptom tie-in [105]. …”
Section: Probiotics and Respiratory Allergymentioning
confidence: 99%
“…In adult patients with seasonal allergic rhinitis, probiotics modulated immune responses; they have the potential to alleviate the severity of symptoms31). However, other studies showed that probiotics provided few clinical benefits and did not alleviate the symptoms or reduce the use of medication32,33).…”
Section: Clinical Efficacy Of Probiotics On Allergic Diseasesmentioning
confidence: 99%
“…For instance, Lactobacillus paracasei-33 caused increase in quality of life parameters, Bifidobacterium longum BB536 caused relief in rhinorrhea, nasal blockage and composite scores, and reduction in ocular and nasal symptoms in Japanese cedar pollinosis, Lactobacillus gasseri altered serum IgE concentration, Lactobacillus casei DN-1 14 001 reduced number of AR episodes in children with AR [82]. However, others showed little clinical benefit of probiotics use [83]. Insufficient and non-robust data available so far clearly warrants further research to support use of probiotics in the treatment of AR.…”
Section: Capsaicin Desensitization Complementary Alternative Treatmmentioning
confidence: 99%